2014
DOI: 10.1017/s1431927614000014
|View full text |Cite
|
Sign up to set email alerts
|

Performance of High-Resolution SEM/EDX Systems Equipped with Transmission Mode (TSEM) for Imaging and Measurement of Size and Size Distribution of Spherical Nanoparticles

Abstract: The analytical performance of high-resolution scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDX) for accurate determination of the size, size distribution, qualitative elemental analysis of nanoparticles (NPs) was systematically investigated. It is demonstrated how powerful high-resolution SEM is by using both mono- and bi-modal distributions of SiO2 airborne NPs collected on appropriate substrates after their generation from colloidal suspension. The transmission mode of the SEM (TSEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…More details on this method and instrumental approach, with advantages and disadvantages, have already been reported. [26][27][28] Dynamic laser scattering (DLS) analysis. DLS measurements were made using a Delsa Nano™ C Analyzer (Beckman Coulter) equipped with a 638 nm diode laser and a temperature control.…”
Section: Methodsmentioning
confidence: 99%
“…More details on this method and instrumental approach, with advantages and disadvantages, have already been reported. [26][27][28] Dynamic laser scattering (DLS) analysis. DLS measurements were made using a Delsa Nano™ C Analyzer (Beckman Coulter) equipped with a 638 nm diode laser and a temperature control.…”
Section: Methodsmentioning
confidence: 99%
“…At such low PE voltages, the particles at the nanoscale are no longer transparent for the electrons and the resulting contrast in the transmission T-SEM micrographs is superior to that corresponding to the high-resolution micrographs obtained e.g., with an in-lens detector. More details on the performance of the T-SEM mode used in this paper can be found in [13][14][15]. A representative example is shown in Fig.…”
Section: Electron Microscopy and X-ray Spectroscopy Analysismentioning
confidence: 99%
“…This is the volume where the detected X-ray photons originate from and is typically in the range of roughly 1 μm 3 . However, recently, it has been demonstrated that SEM working in the transmission mode (TSEM) enables traceable determination of nanoparticle size distribution [23,24]. Coupling EDX to TSEM and employing thin electron transparent samples, e.g.…”
mentioning
confidence: 99%